Narrative Mechanisms and Digital Technologies in Health Communication: A Systematic Review of Shuo Zhou’s Research Contribution - Zhang, Yiyi (The Journal of Medicine, Humanity and Media, 2026)
New technology brings new narrative studies. This review synthesizes Shuo Zhou’s research on health communication, highlighting the integration of narrative mechanisms and digital technologies. It demonstrates how narrative features, such as character identification, moral framing, and personalization, influence cognition, emotion, and health behaviors. This study also explores technology-mediated interventions, including virtual reality, AI, and mobile health applications, showing how digital platforms enhance engagement and behavioral outcomes. Combining quantitative and qualitative methods, Zhou's research bridges theory and practice, emphasizing interdisciplinary integration, cultural sensitivity, and evidence-based strategies. This review emphasize the importance for designing effective, inclusive, and technologically informed health interventions.